IMPLEMENTATION OF LEARNING MANAGEMENT SYSTEMS AND ITS ROLE IN THE EDUCATIONAL PROCESS IN THE REPUBLIC OF UZBEKISTAN - Lola Alimdzhanovna Kadirova (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes and compares modern learning management systems (LMS). Their disadvantages and advantages are revealed. The system of advantages of using the systems is visually demonstrated. The role of LMS in the system of higher education in the Republic of Uzbekistan is determined. The possibility of LMS application in inclusive education is separately noted.